The Influence of Motivation and Work Environment on Employee Performance: Study at a Cleaning Service Company in Bandung - Ine Julia; Windi Matsuko Danasasmita (Majalah Bisnis & IPTEK, 2023)
The inception of this study can be traced back to the difficulties encountered by a cleaning service company located in Bandung. The challenges encompass diminished employee motivation and an unfavorable work environment, predominantly attributable to factors associated with human error. The concerns above had an adverse effect on the productivity of the employees. This study aims to assess the impact of motivation and work environment on the performance of employees. The employed research methodology entails a quantitative approach characterized by a descriptive and empirically verifiable framework. The sample population comprises 46 respondents employed in a company located in Bandung. In order to acquire corroborative data and information, primary data is utilized, which is directly gathered from employees of a cleaning service company located in Bandung. The statistical methodology utilized in this study is multiple linear regression. According to the study's findings, all statement items demonstrate validity and reliability, as indicated by correlation coefficients exceeding the predetermined threshold. Motivation exerts a substantial impact on the performance of employees. The work environment can also influence employee performance. Therefore, the present study demonstrates the influence of motivation and work environment on employee performance within a cleaning service company in Bandung.